Study on the porosity issues in metal 3D printing - Yap, Timothy Shi-Jie (2017)
Selective laser melting of stainless steel 316L (SS316L) cubes was conducted using various sets of process parameters, varying in laser power, hatch spacing and laser scan speed. The cubes were measured for their density, roughness, and hardness. It is recommended to print SS316L parts using 110 J/mm3, a hatch spacing of 100 μm, a layer thickness of 50 μm, a power of 400 W, and a laser scan speed of 727.3 mm/s. These parameters result in a good tradeoff of density, hardness, and roughness values: a density of approximately 7.92 g/cm3 and a Rockwell B hardness of 91 can be achieved. A top surface Ra of 20 μm and a side surface Ra of 30 μm can be achieved. These experiments were conducted on the SLM 500 although it can be recommended for all SLM machines that can achieve the above process parameters on SS316L powder. Using other parameters will result in a mixture of the following results: lower density (or higher porosity), lower hardness, and/or high roughness. It is important for any printed part to have a high density to achieve better mechanical properties such as high toughness or tensile strength. It is also important for roughness to be low so as to minimize post-processing work. The above findings will help engineers to print optimal SS316L parts while minimizing time and effort spent on trial-and-error to find the correct set of process parameters.